Two Hundred Twenty-Six Consecutive Deep Brain Stimulation Electrodes Placed Using an "Asleep" Technique and the Neuro|MateTM Robot for the Treatment of Movement Disorders. Issue 5 (6th July 2020) - Moran, Catherine; Sarangmat, Nagaraja; Gerard, Carter S; Barua, Neil; Ashida, Reiko; Woolley, Max; Pietrzyk, Mariusz; Gill, Steven S
Abstract: BACKGROUND: Robotics in neurosurgery has demonstrated widening indications and rapid growth in recent years. Robotic precision and reproducibility are especially pertinent to the field of functional neurosurgery. Deep brain stimulation (DBS) requires accurate placement of electrodes in order to maximize efficacy and minimize side effects. In addition, asleep techniques demand clear target visualization and immediate on-table verification of accuracy. OBJECTIVE: To describe the surgical technique of asleep DBS surgery using the Neuro|Mate TM Robot (Renishaw plc, Wotton-under-Edge, United Kingdom) and examine the accuracy of DBS lead placement in the subthalamic nucleus (STN) for the treatment of movement disorders. METHODS: A single-center retrospective review of 113 patients who underwent bilateral STN/Zona Incerta electrode placement was performed. Accuracy of implantation was assessed using 5 measurements, Euclidian distance, radial error, depth error, angular error, and shift error. RESULTS: A total of 226 planned vs actual electrode placements were analyzed. The mean 3-dimensional vector error calculated for 226 trajectories was 0.78 +/− 0.37 mm. The mean radial displacement off planned trajectory was 0.6 +/− 0.33 mm. The mean depth error, angular error, and shift error was 0.4 +/− 0.35 mm, 0.4 degrees, and 0.3 mm, respectively. CONCLUSION: This report details our institution's method for DBS lead placement in patients under general anaesthesia using anatomical targeting without microelectrode recordings or intraoperative test stimulation for the treatment of movement disorders. This is the largest reported dataset of accuracy results in DBS surgery performed asleep. This novel robot-assisted operative technique results in sub-millimeter accuracy in DBS electrode placement.